"So, is that your 'relative' or mine?" A political-ecological critique of census-based area deprivation indices. (October 2015) - Fu, Mengzhu; Exeter, Daniel J.; Anderson, Anneka
Abstract: Census-based deprivation indices have been widely used in Aotearoa/New Zealand, Canada and UK to measure area-based socio-economic inequalities. This paper examines the indicators used in census-based area deprivation indices using a political ecology approach. We question whether the current indicators of deprivation derived from census data are meaningful for the all age groups and minority groups in the population, with a particular focus on deprivation indicators used in New Zealand, Canada and the United Kingdom. We comparatively reviewed methodological papers and reports that describe the indicators of deprivation in Aotearoa/New Zealand, Canada and the UK from 1975 to 2014. We consider the relationship between the notion of standards of living and measurements of deprivation and explore how hegemonic cultural constructs are implicit in measures of deprivation that privilege a Eurocentric, ageist and gender normative construction of statistics. We argue for more political ecological analyses to studying the relationship between social inequalities, geographies, health inequities and political economy to transform structures of oppression and inequality. This requires turning the analytical gaze on the wealthy and privileged instead of defaulting into deficit models to account for inequality. Studies of deprivation and inequality would benefit from understanding the processes and operations of power in the (re)production of socio-economic and health inequities to inform holistic strategies for social justice. Highlights: Critical, political ecological, review of census-based area deprivation indices. Evaluates relevance of deprivation indicators for people from minority groups. Indices covered highlight lack of consideration of customary standards of living. Support theories that focus on privilege rather than deficit models of inequalities.